Military chaplaincy in the South African Defence Force during the Namibian War of Independence, 1966-1989 - Wessels, Andre; Bredenkamp, Izette (Faculty of Humanities, University of the Free State, 2009)
Abstract not available
Keywords: Military chaplaincy; South African Defence Force; Namibian war; War of independence